Uma metodologia de análise de textos escolares: um exemplo com conteúdo de Física - Helena Caldas; Edith Saltiel (Universidade do Minho, 2001)
This work presents and describes a methodology of analysis of didactic texts, having as starting point the results of investigations about the tendencies of the students´ common sense knowledge on a specific subject matter in science. The consequences of such methodology will be evoked as much at the research level as at the pedagogic level using the example of a topic in physics, specifically that of the phenomenon of the kinetic friction between solids treated in books used in the higher education.